Pengaruh Kompetensi Aparatur Desa, Sistem Pelaporan Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa Di Desa Se-Kecamatan Denpasar Utara - Ni Kadek Rosita Asriva Dewi (UNHI Press, 2023)
The village government is obliged to take responsibility for the village funds it manages in accordance with applicable rules. This responsibility is often referred to as accountability. Accountability is a means of controlling all activities carried out by the apparatus as a form of responsibility to the people. The importance of accountability makes researchers interested in examining the relationship between apparatus competence, reporting system, and clarity of budget targets on accountability. The results of the study indicate that the competence of the village apparatus that is well developed will increase accountability. A well-designed reporting system creates accountability, and clearly defined budget goals increase accountability.